ANALISIS KINERJA PELAYANAN PELABUHAN NUSANTARA RAHA KABUPATEN MUNA - Muh. Anando Kolawano; Romy Suryaningrat Edwin; La Ode Muhamad Nurrakhmad Arsyad; Muhammad Thahir Azikin; Adris Ade Putra; Asrullah Tondasi (Jurnal Teknik Sipil dan Arsitektur, 2026)
Nusantara Raha Port is a port located in Raha City, Muna Regency, Southeast Sulawesi. Nusantara ports are one of the strategic and most important aspects for various economic and government activities in advancing the regional economy and development. Services at Nusantara Raha Port must be improved to continue supporting transportation activities and increasing user satisfaction. This study aims to understand the service quality of the port at Nusantara Raha Port based on user perceptions. The analysis was conducted through the calculation of CSI (Customer Satisfaction Index) and IPA (Importance Performance Analysis). The study results obtained a user satisfaction level or CSI weight at Nusantara Raha Port for 23 service aspects valued at 73% and classified as satisfied. The study results using the IPA method have a mapping of the average weight of service attributes divided into several quadrants with details, namely in Quadrant I as many as 7 attributes where the level of importance is high and the performance level is low, for Quadrant II as many as 7 attributes with high importance and high performance, for Quadrant III as many as 6 attributes where importance is low and performance is also low, and for Quadrant IV as many as 3 attributes where importance is low while performance is high. Based on the service performance of Nusantara Raha Port analyzed using the IPA method, the results show a performance of 3.66 and importance of 4.23, which meets the scale criteria with the category of good and important. Keywords : Nusantara Raha Port, Service Satisfaction, Interest Performance Analysis, Customer Satisfaction Index.